Regional effects of an emissions-reduction policy in China: Taxes, subsidies and the method of financing - Anping Chen; Nicolaas Groenewold (European Regional Science Association (ERSA), 2013)
The issue of the possible adverse effects of a reduction in pollution on the economy is a very real one for China, given its public commitment to substantial cuts in CO2 emissions by 2020. An important part of this issue is the regional dimension C the pollution reduction is likely to have significantly different effects across the regions and so possibly exacerbate the already large and persistent inter-regional disparities in China. Policy choices will therefore be complicated and will need to be carried out with a clear understanding of the impact of alternative policies at national and regional levels. One important policy choice which has received little, if any, attention in the regional context is the one between a tax on pollution and a subsidy on abatement activity. We help elucidate this policy choice by exploring the tax-subsidy issue in a small theoretical model which captures some of the salient features of the Chinese regions and the tax/expenditure system and which we solve numerically based on a parameterisation achieved using data for the Chinese economy. We find that (i) The adverse economic effects of a reduction in emissions are greater in the interior than in the coast but (ii) the coast is worse-off than the interior due to relative price changes and the effects of the government budget constraint; (iii) the effects of a tax on macroeconomic variables such as wages, profits and output are greater than they are in the case of a subsidy, particularly in the short run but (iv) there is little to choose between the two instruments as far as welfare is concerned.
Keywords: 330; Emissions Reduction; Tax; Subsidy